Personnel qualimetric assessment of the consumer information center of insurance organization - Dolzhanskiy, Anatoliy; Bondarenko, Oksana; Vusatenko, Тatyana (Technology audit and production reserves, 2021)
The object of the study was the system for assessing the quality of the information service personnel of the insurance company. When determining the approaches to improving the relevant components of the quality system, the organization took into account that the personnel assessment process is the most painstaking, complex and lengthy aspect of the firm’s activities. Mistakes in such a matter can not only cost one person’s dissatisfaction, but affect a certain number of problems regarding the stable functioning of an entire institution. The complexity of this issue lies in the absence, in general, of universal quantitative assessment criteria and the strong influence of the «human factor», which necessitates the use of expert qualimetric approaches with an increase in the objectivity of the assessment. In this regard, the work was aimed at developing an objective system for assessing personnel on the example of the information service of one of the insurance companies in Ukraine using qualimetric methods. Tools for the integrated qualimetric assessment of the quality of the information center employees’ activities, which consist in determining of the appropriate list and significance of the personnel performance quality indicators, were proposed with an analysis of the possibility of their identification and measurement. Additionally, it is recommended to take into account independent control using «mystery shopper», as well as the self-esteem of workers. The obtained results were used in the development of the Methodology (Procedure) of the quality system for the assessment of activities and personnel certification. The use of the outlined approaches makes it possible to increase the level of satisfaction of customers and consumers of insurance services, to increase the economic efficiency of the organization’s activities, to differentiate personnel by the quality of work with appropriate personal encouragement for training, self-realization and work productivity. The deliverables may be useful to organizations in the relevant domain and may be applicable in other similar settings.